Effect of Boron addition on the microstructure, phase transitions and magnetocaloric properties in Gd-Si-Ge alloy. (May 2018) - Prabahar, K.; Kumar, N. Pavan; RajKumar, D.M.; Arumugam, S.; Manivel Raja, M.
Abstract: The Gd5 Si2 Ge2 Bx (0 < x ≤ 0.125) alloys were investigated to study the influence of Boron addition on the structure, microstructure, magnetic and magnetocaloric properties. Except x = 0.05 alloy, all the other Boron containing alloys under study displayed the presence of major monoclinic Gd5 Si2 Ge2 -type phase along with low volume fraction of hexagonal GdSi-type (5:5 H) secondary phase at room temperature (RT). In the case of alloy with x = 0.05, monoclinic Gd5 Si2 Ge2 -type and orthorhombic Gd5 (Si, Ge)4 type mixed phases along with low volume fraction of Gd5 Si3 -type (5:3 H) secondary phase were observed at RT. The structural transition (Ts ) (orthorhombic to monoclinic) and the Curie transition (TC ) of the monoclinic phase in the x = 0.05 alloy occurred at 293 K and 305 K respectively. These transitions occurred at relatively higher temperatures than those reported in parent Gd5 Si2 Ge2 alloy. At higher concentrations of Boron (x > 0.05), both the transitions, Ts and TC shifted to lower temperatures. A maximum magnetic entropy change of 13.6 J/(kg-K) (at 293 K) and refrigerant capacity (RC) of 378 J/kg were obtained in Gd5 Si2 Ge2 B0.05 alloy which conveys that this alloy has an edge over the parent alloy in terms of operating temperature and refrigeration capacity. Highlights: Effect of Boron addition on the microstructure, magneto-structural transitions and magnetocaloric properties were investigated in Gd5 Si2 Ge2 Bx (0 < x ≤ 0.125) alloys. For x = 0.05 alloy, the structural transition temperature reached 293 K which is higher than that of the parent Gd5 Si2 Ge2 alloy. A maximum isothermal magnetic entropy change (ΔSM ) obtained in Gd5 Si2 Ge2 B0.05 is 13.6 J/(kg-K) at Δ H  = 0–5 T along with a significantly high RC value of 378 J/kg near room temperature which makes it more promising for commercial application for magnetic refrigeration technology near room temperature.